Pengaruh Manajemen Pengetahuan Terhadap Peningkatan Inovasi Dan Kualitas Pelayanan RSUD Kabupaten Serang - Elisa Anggraeni, Riyan M. Faris, Heti Mulyati, (Jurnal Ekonomi, 2020)
This study aims to determine and analyze the role of knowledge management in improving innovation and service quality, as well as analyzing the effect of innovation on service quality in the Drajatprawiranegara regional hospital in Serang Regency. In this study the analysis of data processing using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of the analysis (SEM-PLS) explain that there is an influence between knowledge management on innovation where the application of optimal knowledge management will increase innovation in the health service process. There is a significant indirect effect between knowledge management on service quality, but innovation influences service quality. Therefore human resource management in Drajat Prawiranegara hospital must be carried out comprehensively. Cooperation between fields of work, be it medical, doctor and non-medical workers must be optimal in facing challenges and demands from changing health services.